2003
DOI: 10.1002/em.10198
|View full text |Cite
|
Sign up to set email alerts
|

Genetic toxicity of methamphetamine in vitro and in human abusers

Abstract: Methamphetamine (METH) is a widely abused psychomotor stimulant. Although numerous studies have examined METH-induced neurotoxicity, its ability to produce genotoxic effects has not been evaluated. In this article, we report on the genotoxicity of METH in vitro and in human METH abusers. METH induced his(+) revertants in Salmonella typhimurium strains TA98 and TA100, and increased the frequency of hprt mutants, micronuclei, and sister chromatid exchange (SCE) in cultured Chinese hamster ovary K1 (CHO-K1) cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 41 publications
(40 reference statements)
1
6
0
Order By: Relevance
“…Another lifestyle variable that potentially could produce genotoxic effects is the use of recreational and illicit drugs such as methamphetamines (METHs), cocaine, marijuana and heroin (69). However, there is as yet only one study reported showing that MN in PBL are increased in METH users (70). This study on 76 long-term METH abusers and 98 unexposed controls demonstrated that total METH exposure was positively correlated with MN and sister chromatid exchanges frequencies in ex vivo cultured lymphocytes.…”
Section: Use Of Recreational and Illicit Drugsmentioning
confidence: 82%
“…Another lifestyle variable that potentially could produce genotoxic effects is the use of recreational and illicit drugs such as methamphetamines (METHs), cocaine, marijuana and heroin (69). However, there is as yet only one study reported showing that MN in PBL are increased in METH users (70). This study on 76 long-term METH abusers and 98 unexposed controls demonstrated that total METH exposure was positively correlated with MN and sister chromatid exchanges frequencies in ex vivo cultured lymphocytes.…”
Section: Use Of Recreational and Illicit Drugsmentioning
confidence: 82%
“…Other agents induce much higher AIMF in repair-proficient cells. Methamphetamine showed an AIMF of 13/10 6 in the CHO K1 line (32). The dietary supplement chromium picolinate produced an AIMF of 58/10 6 surviving cells in the AA8 line (14).…”
Section: Discussionmentioning
confidence: 97%
“…A recent comprehensive review (Drug Effectiveness Review Project, 2005) of medication treatment for ADD/ADHD concluded that there was no evidence on the longterm safety of the medications used in ADD/ ADHD treatment and that good quality evidence is lacking that drug treatment improves academic performance or risky behaviors on a long-term basis, or in adolescents or adults. In relation to the findings of this review, one of the latest studies (El-Zein et al, 2005) concluded that "the lack of research on long-term effects of methylphenidate [Ritalin] use in humans warrants great concern" (p. 7) because they discovered that after only three months on Ritalin, 100% of children experienced chromosomal aberrations which could increase cancer risk, not unlike the genetic damage that has been found in adult methamphetamine users (Li, Hu, Chen, & Lin, 2003).…”
Section: Medication Compared To Neurofeedbackmentioning
confidence: 94%